On 3D printed biomedical sensors for non-enzymatic glucose sensing applications. (August 2022) - Kumar, Vinay; Kumar, Ranvijay; Singh, Rupinder; Kumar, Pawan
Some studies have been reported in the recent past on smart sensors for non-enzymatic glucose sensing applications. Nevertheless, little has been reported on the in-house development of low-cost 3D printed smart biomedical sensors with tunable sensitivity. This study reports investigations on the in-house, low-cost fabrication of polyvinyl difluoride (PVDF) matrix-based 3D printed tunable non-enzymatic glucose sensors. For fabrication of smart sensors, Cu (4%) doped ZnO nanoparticles have been reinforced (in different weight proportions (wt%) in PVDF matrix through melt processing. The results suggest that 4% reinforcement (of 4% Cu doped-ZnO), processed at 190°C, 40 rpm screw speed on twin screw extrusion (TSE) followed by post heat treatment (HT) at 60°C are the best settings for fabrication of feedstock filaments (for bio-sensor 3D printing). Finally, a PVDF-based sensor to support bioreceptor and transducer requirements has been successfully prepared (with 4D properties (i.e. one-way programing feature), optical, morphological, bond strength, piezoelectric and mechanical characteristics). The 3D printed electro-active sensor, (of selected composition) resulted in acceptable mechanical, piezoelectric, and dielectric properties (modulus of toughness (MoT) 1.46 MPa, Young's modulus (YM) 1221.7 MPa, piezoelectric coefficient 19.3pC/N and dielectric constant 6.5). The results have been supported by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), current-voltage-resistance (I-V-R), and Fourier transformed infrared (FTIR) analysis. Graphical Abstract